Optimasi Parameter Proses pada 3D Printing FDM terhadap Akurasi Dimensi Filament PLA Food Grade - MALINDA CHRISTILIANA; Pristiansyah; Yudi Oktriadi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
3D printing is manufacturing process technology that is widely developed to make a rapid prototype according to the desired design, one of which is FDM (Fused Deposition Modeling) technology. The type of filament used in this study was filament PLA food grade. This study aims to obtain optimal parameters for FDM 3D printing machines in terms of dimensional accuracy. The method used in this process parameter optimization research is the Taguchi L27 OA method. The process parameters used are nozzle temperature, layer thickness, print speed, infill rate, and temperature based plate. The results of research that have been conducted show the optimal process parameter values ??for dimensional accuracy of the specimen height was nozzle temperature (185°C), layer thickness (0,20mm), print speed (40mm/s), infill rate (8%), and temperature based plate (40°C) .